Analogue Optical Spatiotemporal Differentiator. Issue 10 (7th March 2021) - Zhou, Yi; Zhan, Junjie; Chen, Rui; Chen, Wenjie; Wang, Yubo; Shao, Yifan; Ma, Yungui
Abstract: As a significant part in optical computation, analogue optical spatial/temporal differentiators could play a great role in all‐optical signal processing, feature extraction, and optical storage. In the past few years, they have experienced rapid development but mostly for a single function. For many scenarios, optical computation with integrated functionalities is highly desired. In this work, an analogue optical spatiotemporal differentiator utilizing all‐dielectric multilayer is proposed. The film stack is specifically engineered to satisfy the requirements for both spatial and temporal transfer functions of the ideal differentiator. The time‐space performance of the device is numerically examined from the output field profile of the classical Gaussian beam or pulse. A wavelength‐scale high resolution for edge detection is attained using the integrated differentiator. This work may pave a potential way to establish ultracompact, high‐bandwidth, and real‐time optical multiple functional computation systems. Abstract : In this work, the authors present an analogue optical spatiotemporal differentiator based on all‐dielectric multilayer film. The spatial and temporal transfer functions of the device are carefully designed to tally with transfer functions of the ideal differentiation. The Gaussian beam/pulse is adopted to verify the performance of the differentiator. The edge detection ability of the device is also investigated.